Academic Motivations in Junior High School Refreshing Day - Djajasoepena, Rafie; Setiawan, Iwan; Triawan, Farid; Redi, Anak Agung Ngurah Perwira; Fernandez, Nikolas Krisma Hadi; Prasetyo, Ilham; Alibasa, Muhammad Johan; Wandy, Wandy (Journal of Community Services: Sustainability and Empowerment, 2024)
Motivation is a crucial factor in education as it stimulates, guides, and channels purposeful behavior driven by biological, emotional, social, and cognitive factors. Motivation can be a key element of a student’s achievement. This study explores the role of motivation in academic achievement and describes a community service program undertaken at SMP Negeri 174 Jakarta.. This initiative aims to motivate students before their final exams by sharing success stories of effective study habits and providing tips for exam preparation. The community service activities commenced in late March 2024 and concluded in May 2024. Over 200 participants, consisting of year-9 students, took part in the event, which began in the morning and lasted for two hours, ending before noon. The majority of the resource persons and the organizers were actively involved in the event preparations. The success of this initiative suggests the potential of similar programs to motivate students in the future.